Atlantic near‐term climate variability and the role of a resolved Gulf Stream. Issue 8 (30th April 2016) - Siqueira, Leo; Kirtman, Ben P.
Abstract: There is a continually increasing demand for near‐term (i.e., lead times up to a couple of decades) climate information. This demand is partly driven by the need to have robust forecasts and is partly driven by the need to assess how much of the ongoing climate change is due to natural variability and how much is due to anthropogenic increases in greenhouse gases or other external factors. Here we discuss results from a set of state‐of‐the‐art climate model experiments in comparison with observational estimates that show that an assessment of predictability requires models that capture the variability of major oceanic fronts, which are, at best, poorly resolved and may even be absent in the near‐term prediction of Intergovernmental Panel on Climate Change class models. This is the first time that air‐sea interactions associated with resolved Gulf Stream sea surface temperature have been identified in the context of a state‐of‐the‐art global coupled climate model with inferred near‐term predictability. Key Points: Ocean dynamics play a key role in decadal climate variability once air‐sea interactions associated with ocean fronts and eddies are resolved IPCC class climate models have limited ability to capture decadal variability in the North Atlantic due to relatively low ocean resolution